1999
DOI: 10.1034/j.1399-6576.1999.430405.x
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of lidocaine and bupivacaine in breast milk following epidural anesthesia for cesarean delivery

Abstract: This study documents the magnitude of excreted lidocaine, bupivacaine and PPX in breast milk, and indicates that the use of both lidocaine and bupivacaine for epidural anaesthesia is safe with regard to breast-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 6 publications
1
19
1
1
Order By: Relevance
“…After epidural administration, local anaesthetics showed acceptable milk-to-plasma ratios of 1.1 for lignocaine (lidocaine) and 0.34 for bupivacaine (Ortega et al, 1999) and 0.25 for ropivacaine (Matsota et al, 2009), which are considered safe (Rathmell et al, 1997). Use of epidural analgesia (local anaesthetic ± fentanyl) during labour (Chang & Heaman, 2005 Level III-3) or as PCEA after Caesarean section (Matsota et al, 2009 Level IV) did not influence neurobehavioural scores in healthy term infants.…”
Section: Other Medications Related To Pain Reliefmentioning
confidence: 99%
“…After epidural administration, local anaesthetics showed acceptable milk-to-plasma ratios of 1.1 for lignocaine (lidocaine) and 0.34 for bupivacaine (Ortega et al, 1999) and 0.25 for ropivacaine (Matsota et al, 2009), which are considered safe (Rathmell et al, 1997). Use of epidural analgesia (local anaesthetic ± fentanyl) during labour (Chang & Heaman, 2005 Level III-3) or as PCEA after Caesarean section (Matsota et al, 2009 Level IV) did not influence neurobehavioural scores in healthy term infants.…”
Section: Other Medications Related To Pain Reliefmentioning
confidence: 99%
“…Newborn serum concentrations were unable to be assessed due to transplacental passage of LA, but APGAR scores and 24-hour clinical examinations were normal in the study population. 9 • Opioid: The serum concentration of opioid, which is determined by the dose of spinal or epidural analgesia, is usually minuscule, if at all present. Madej et al found that after a fentanyl bolus of 100 mcg into the epidural space for elective cesarean delivery, the drug in maternal breast milk was undetectable at the time of first request for postoperative analgesics by the mother.…”
Section: A With Neuraxial Anesthesiamentioning
confidence: 99%
“…Studies evaluating IV, epidural, and dental administration of lidocaine suggest that nursing after these procedures is generally safe [18][19][20]. Nevertheless, patients may wish to consider pumping and discarding milk from the affected breast for up to 12-24 hours after core needle biopsy.…”
Section: Imaging-guided Proceduresmentioning
confidence: 99%